دلالة الاستفهام بالهمزة على ظل المعنى في القرآن الكريم = The indication of interrogation using ‘Hamza’ on the shades of meaning in the Holy Qur’an - Saleh Al-Tijani, Saada Al-Senussi; Ali, Asem Shehadeh Saleh (Electronic Interdisciplinary Miscellaneous Journal (EIMJ), 2024)
جاءت الدراسة بعنوان "دلالة الاستفهام بالهمزة على ظل المعنى في القرآن الكريم: دراسة تحليلية"، فدونت الباحثة الآيات المختارة من كتاب محمد عبد الخالق عضيمة (دراسات لأسلوب القرآن الكريم)، وهي الآيات الموجودة تحت عنوان: همزة الاستفهام مع همزة القطع الأولى مفتوحة والثانية مكسورة وهمزة الاستفهام مع همزة القطع مفتوحتان، وقد بلغ مجموع الآيات 50 آية؛ وسوف نتطرق في هذا البحث إلى شرح بعض الأمثلة لكل من نوعي الهمزة، ويتبع البحث المنهج الوصفي التحليلي، ويهدف هذا البحث إلى تبيين الأبعاد الدلالية لهمزة الاستفهام ومدى ارتباطها بالدرس اللغوي الحديث، وذلك من خلال التقصي في كتب التفاسير المأثورة والإعراب والقراءات، وتوضيح المعاني التي تخرج فيها همزة الاستفهام عن معناها الأصلي إلى معانٍ أخرى؛ كالتقرير والإنكار والأمر ... إلخ، ومدى مناسبة هذه المعاني للسّياق القرآني التي وردت فيه الهمزة الاستفهامية وقد توصل البحث إلى الارتباط الوثيق بين المعنى الذي خرجت له الهمزة وبين التحليل الذي جمع من الكتب المختلفة. ***** The study is titled by: The Indication of the Interrogative ‘Hamza’ on the Shades of Meaning in the Holy Qur’an: An Analytical Stud. where the researchers wrote down selected verses from the book of Muhammad Abd al-Khaleq Adhimah (Studies on the Style of the Holy Qur’an). The reference is made to the verses found under the title: The interrogative ‘Hamza’ with hamzat al-Qat`, the first having Fathah and the second Hamza having Kasrah as well as the interrogative Hamzat alqat’ with both Hamzat having Fathah. The total number of verses is 50. In this study, the explanation of some examples of each of the two types of Hamza is addressed. The research follows the A descriptive and An analytical approach and aims to clarify the semantic dimensions of the interrogative Hamza and the extent to which it connects to the modern linguistic lesson. This is accomplished by investigating the books of famous Tafasir (exegesis), I`rab (Inflection), and Qira’at and clarifying the meanings where the interrogative Hamzah indicates meanings different from the meanings that it usually indicates, such as declaration, denial, command, etc, and investigating the suitability of these meanings to the Qur’anic context in which the interrogative Hamza appeared. The research concluded a close connection between the meaning which the Hamza indicates and the analysis collected from various books.